Joint Education Provision: A Relief or Challenge to Quality Education Services in Uganda. “A Study in Buganda Region”. - Sempungu, Godfrey (2024)
The National Constitution of Uganda underscores the fact that education is a right of every Ugandan. The same document also stipulates the role of the Government and other stakeholders in providing education. It is from this mother document that also the other key providers of education services derive their mandate. In Uganda, providers of education are either private or public. In some cases, the government takes over the management and day-to-day running of some schools whose founder body is private. This is mostly for those schools that are founded by the religious bodies. Hence the coining of the term ‘government-aided’ schools. Even in the previously entirely public-owned schools, the government has introduced cost sharing as it cultivates the culture of having the parents too, share in the task of shouldering some operational costs like lunch & scholastic materials for their children among others. Hence the purely public school has quickly faded off the Ministry of Education vocabulary and government-aided has come to be the key term embracing all schools with a government attachment. Grounded in the Ugandan education system’s practice of joint education service delivery, without losing sight of the bulk of private education providers, this study sought to test whether the quality of education delivered today is better than what it would be if one stakeholder provided the service. The study, in general, investigated the problems that affect the Ugandan school system, reviewed the government's position in lower levels of academia, and gave policy recommendations and suggestions for boosting school performance in light of the current performance. A low resource base is reported as one of the key problems that Ugandan schools still have to grapple with. It in turn has accounted for substandard infrastructure, poor library systems, inadequate teacher remunerations, and appalling student housing problems in some schools, among other challenges. Government stewardship through the Ministry of Education was also found wanting in some aspects. Increasing funding to the education sector was one of the recommended policy interventions. Consultation of all stakeholders even those in the private sector was highly encouraged to foster unity and flatten the ground between different school ownerships. This is projected to reduce the gap between private and public institutions and build a more sound education system founded in performance & qualitative delivery as opposed to institutional ownership. The coverage of this study could have been wider, but time and monetary resources were key hampering factors to a more exhaustive and comprehensive coverage. It is therefore my strong recommendation that a corrective study ought to be done. This should raise more palliative approaches to improving performance between the public and private sectors. The government also needs to realize that Uganda is a developing country and education is a priority that is highly needed to achieve and sustain development. They should therefore control most of the educational institutions as opposed to leaving the majority of them in the hands of private institution owners. The government too needs to improve its performance as regards the role of stewardship in its institutions. As far as achieving the objectives of the study is concerned, the study was largely successful.